2017
DOI: 10.18502/sjms.v12i3.915
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Iron, Total Iron Binding Capacity and Transferrin Saturation Percent in Sudanese Females Newly Diagnosed with Breast Cancer at Khartoum Oncology Hospital: A case- control study

Abstract: Background: Iron is a vital constituent of cells but in excess may be harmful and is associated with a raised risk for some malignant diseases including breast cancer. We aimed to study changes in iron profile in Sudanese females newly diagnosed with breast cancer. Methods: A case-control study in which serum iron, Total Iron Binding Capacity (TIBC), and transferrin saturation percent were measured for fifty females with breast cancer referred to Khartoum Oncology Hospital and seventy apparently healthy female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…For example, breast cancer patients have significantly higher levels of iron than normal controls. 67,68 Thus, cancers with high levels of iron might be more susceptible to AA through increased production of free radicals via LIP. In a research reported by Xia et al, high dose AA, in the presence of iron, leads to the formation of highly ROS resulting in cell death of multiple myeloma cells.…”
Section: Pro-oxidantmentioning
confidence: 99%
“…For example, breast cancer patients have significantly higher levels of iron than normal controls. 67,68 Thus, cancers with high levels of iron might be more susceptible to AA through increased production of free radicals via LIP. In a research reported by Xia et al, high dose AA, in the presence of iron, leads to the formation of highly ROS resulting in cell death of multiple myeloma cells.…”
Section: Pro-oxidantmentioning
confidence: 99%
“…The higher hepcidin and hence lower ferroportin levels, i.e., a high hepcidin/ferroportin ratio, eventually leads to an increase in ferritin expression and consequent iron overload [ 19 , 20 ]. Transferrin levels were also found to be altered in breast cancer cases [ 8 , 21 , 22 ]. Elevated concentrations of estrogen in breast tissue, which disrupts intracellular iron metabolism, results in excess iron that can initiate the generation of superoxide anions and the conversion of ferritin-bound Fe 3+ to Fe 2+ , leading to estrogen-induced oxidative stress on nucleic acids followed by carcinogenesis ( Figure 2 ) [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%